PERNIKAHAN WANITA HAMIL DI LUAR NIKAH DITINJAU DARI PERSPEKTIF MAQASHID SYARIAH - Samanta Debora; Fakhry Emil Habib (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
Marriage of pregnant women out of wedlock is currently a phenomenon that often occurs in society. In general, the family will make the decision to marry the woman off to cover the family's disgrace. KHI, as the material legal basis in Islamic law legislation in Indonesia, determines that women who become pregnant due to adultery are allowed to marry the man who impregnated them without having to wait for the woman to give birth first. Meanwhile, among Islamic jurisprudence scholars, there is a conflict regarding this matter. Some scholars are of the opinion that it is not permissible to marry a woman who is pregnant because of adultery for reasons of iddah, others allow it because they believe that women who commit adultery do not have an iddah period. Regardless of this difference of opinion, if viewed from the maqashid shari'ah perspective, the validity of the marriage of a pregnant woman out of wedlock is basically closely related to maintaining a good name (hifz al-'irdh), both the good name of the extended family and the good name of the woman herself. and of course the good name of the child who will be born.